Norwegian scabies- A case report - Kedia, Sima Kumari; Mathur, Mahesh (Journal of College of Medical Sciences-Nepal, 2010)
Norwegian scabies is a rare form of a common ectoparasitic infestation of skin. Case report is of importance for the general practicerners point of view and for the information of preventive and social health workers. Key words: Norwegian scabies; ectoparisite. DOI: 10.3126/jcmsn.v6i2.3617 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 47-49